Clinical Features and Overall Survival of Females with Hepatocellular Carcinoma: A Retrospective Study and Review of the Literature in the Association of Southeast Asian Nations - Ratana-Amornpin S; Vilaichone RK; Miftahussurur M; Aumpan N; Kaewkarnjanarat K; Nun-anan P; Chonprasertsuk S; Siramolpiwat S; Bhanthumkomol P; Pornthisarn B; Uchida T; Mahachai V (Dove Medical Press, 2021)
Sarita Ratana-Amornpin,1 Ratha-Korn Vilaichone,1- 3 Muhammad Miftahussurur,3 Natsuda Aumpan,1 Kittipong Kaewkarnjanarat,1 Pongjarat Nun-anan,1 Soonthorn Chonprasertsuk,1 Sith Siramolpiwat,1,2 Patommatat Bhanthumkomol,1 Bubpha Pornthisarn,1 Tomohisa Uchida,4 Varocha Mahachai2,5 1Center of Excellence in Digestive Diseases and Gastroenterology Unit, Department of Medicine, Thammasat University Hospital, Pathumthani, Thailand; 2Department of Medicine, Chulabhorn International College of Medicine (CICM) at Thammasat University, Pathumthani, Thailand; 3Gastroentero-Hepatology Section, Internal Medicine Department, Universitas Airlangga, Surabaya, Indonesia; 4Department of Molecular Pathology, Oita University Faculty of Medicine, Yufu, Japan; 5Gastrointestinal and Liver Center, Bangkok Medical Center, Bangkok, ThailandCorrespondence: Ratha-Korn Vilaichone Tel +662-926-9789Fax +662-926-9793Email Vilaichone@hotmail.co.thIntroduction: Hepatocellular carcinoma (HCC) causes more than 200,000 women deaths annually. This study aimed to investigate the clinical features, provide prognostic factors for female patients with HCC, and performed a literature review on them in the Association of Southeast Asian Nations (ASEAN).Materials and Methods: We conducted a retrospective cohort study of female patients with HCC at Thammasat University Hospital, Thailand between January 2009 and January 2019. Furthermore, important aspects of female patients with HCC in the ASEAN published in PubMed and Scopus up to October 2020 were extensively reviewed.Results: A total of 187 female patients with HCC were included (mean age 65.7± 11.9 years). Elderly females were diagnosed with HCC at a more advanced stage than younger individuals (37.0% vs 23.2%, p=0.049, OR 1.94, 95% CI 1.00- 3.78) and the younger group had a significantly higher overall 2-year survival rate than the elderly group (65.0% vs 45.5%, p=0.03, OR 2.23, 95% CI 1.09- 4.57). Abdominal pain (HR 9.89, 95% CI 2.85- 34.38, p< 0.001), ascites at presentation (HR 2.77, 95% CI 1.11- 6.92, p=0.03), ruptured hepatoma (HR 14.68, 95% CI 12.60- 83.09, p=0.002), advanced-stage HCC (HR 9.74, 95% CI 1.89- 50.26; p=0.007), and serum hypoalbuminemia (HR 4.67, 95% CI 1.62- 13.50, p=0.004) were significantly associated with poor survival rate. From the ASEAN, a total of 543 females HCC patients from 6 studies were extensively reviewed. Chronic hepatitis B infection was among the pre-existing liver disease leading to HCC in ASEAN. HCC in females of the ASEAN occurred most often at an advanced age and had a grave prognosis.Conclusion: HCC affects a large number of females, especially in Thailand and the ASEAN, is diagnosed at an advanced stage and had a grave prognosis. Abdominal pain, ascites, ruptured HCC, advanced-stage HCC, and serum hypoalbuminemia are associated with poor prognosis. Early detection of HCC and prompt treatment in patients at risk could result in better survival outcomes.Keywords: clinical features, outcomes, females, hepatocellular carcinoma